How to use pages on an iPad - Miser, Brad (LiveLessons., 2014)
"How to Use Pages on an iPad (Que Video) teaches you how to get the most out of Apple's Pages app and gives detailed, step-by-step instructions on how to create and share documents like resumes, reports, and newsletters. In this video training, Apple expert Brad Miser starts off with an introduction to the Pages app and its basic functions-how to install the app, obtain an iCloud account, and set up an external keyboard. Then, he moves on to configuring the document's settings, working with the document manager, and creating a simple document, as well as adding and formatting text. After the basics have been covered, the video goes into adding photos, tables, how to collaborate with other Pages users, and finally, how to save and share your work."--Resource description page.